FORMULATION AND EVALUATION OF NICARDIPINE LIQUISOLID COMPACT TABLETS - J.RAMESH,; B.VIJAYA KUMAR,; Y.NARASIMHA REDDY, (International Journal of Pharma and Bio Sciences, 2016)
Main objective of the present study was to enhance the dissolution rate of nicardipine by liquisolid compact method. Nicardipine is practically insoluble in water. Solubility of nicardipine was estimated in different non volatile solvents. Then different formulations were prepared at the drug concentration of 10%, 15% and 20% with excipient ratios (R) 5:1, 7:1, 9:1. Liquisolid compact powder was subjected to angle of repose, Carr’s compressibility index, and hausner’s ratio to determine flow property. Hardness, friability, disintegration time, drug content, dissolution rate are determined. Fourier transforms infrared analysis, x-ray diffraction studies also performed. All the formulations showed acceptable flow property and better drug release. Fourier transform infrared spectroscopy conformed that drug does not interact with excipients which are added in the formulation. X-ray diffraction study proved that nicardipine (crystalline form) converted into amorphous form. From this study it was concluded that liquisolid compact technique improves dissolution rate of nicardipine.